Ἰουδαϊσμός – ἰουδαΐζειν – ἰουδαϊκῶς Sprachliche und semantische Überlegungen im Blick auf Gal 1,13 f. und 2,14 - Sänger, Dieter (Zeitschrift für die neutestamentliche Wissenschaft, 2017)
Since late antiquity there has been diversity in the particulars of the interpretation of the Greek term Ἰουδαϊσμός in Galatians 1,13–14, but the prevailing notion in most cases is that Ἰουδαϊσμός signifies “Judaism”, the religion of the Jewish people. On the contrary, in a provocative article Steve Mason proposed a radical revision of this reading of Ἰουδαϊσμός and its cognates (cf. Gal 2,13–15; 3,28). According to him (and other scholars) there was no category of “Judaism” in the Graeco-Roman World, no “religion” too, and that the Ἰουδαῖοι were understood as an ethnic group comparable to other ethnic groups. Consequently Mason claims that the substantive adjective Ἰουδαῖος has always the ethnic-regional sense “Judean”, never the religious sense “Jew”. To my opinion this view is partly right and partly wrong. Starting from the grammatical and semantic data provided by 2 and 4 Maccabees and attested in the epigraphic record this essay aims at two points: It is argued, first, that due to the fact that Ἰουδαϊσμός and its cognates obviously denote also a religious dimension it seems very unlikely to hold the view of a purely ethnic centered conception of Jewish identity. Further, that the Galatian controversy and the incident at Antioch, described in Gal 2,11–14, reflect a quarrel within the early church about the crucial question concerning the constitutive requirements in regard to the construction, formation, and performance of Christian identity.